Pelaksanaan Kampus Mengajar Angkatan IV dalam Meningkatkan Literasi dan Numerasi - Eltrina Jelita Via; Silveria Mariati; Maria Klara Kolin; Aplonaris Gudu; Maria Kristina Ota (Universitas Teuku Umar, 2025)
The Ministry of Education, Culture, Research, and Technology strives to improve capacity and competence at the elementary and secondary school levels through the numeracy literacy program at the teaching campus. The Teaching Campus Program provides an opportunity for students to contribute directly to improving the quality of elementary and secondary education in Indonesia, especially in terms of literacy and numeracy. This community service activity aims to determine the implementation of the 6th batch of the teaching campus program in improving literacy and numeracy at SMPN 2 Boawae. The method used in this community service activity is to experience directly what happens in the field. This community service activity results in students feeling more motivated when learning literacy and numeracy with the teaching campus activity.